The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.17219/acem/69921
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CCP antibodies and rheumatoid factor in systemic sclerosis: Prevalence and relationships with joint manifestations

Abstract: The prevalence of RF and a-CCP antibodies is relatively high in SSc, and joint involvement occurs frequently. There was a significantly higher prevalence of IgM RF in the group with joint manifestations. About 1/3 of SSc patients had symptoms of arthritis. Arthritis is connected with the presence of a-CCP antibodies, while arthralgia is connected with the presence of IgM RF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
3
9
0
1
Order By: Relevance
“…Further supporting this notion, serum CXCL12 levels were positively correlated with the titers of RF, which is produced by synovial B cells in response to the local environment in the rheumatoid joint 43 . Given that the association of RF positivity with SSc arthropathy is also reported in a previous study, 44 our current data suggest that CXCL12 is involved in the development of SSc arthropathy, like RA and OA.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Further supporting this notion, serum CXCL12 levels were positively correlated with the titers of RF, which is produced by synovial B cells in response to the local environment in the rheumatoid joint 43 . Given that the association of RF positivity with SSc arthropathy is also reported in a previous study, 44 our current data suggest that CXCL12 is involved in the development of SSc arthropathy, like RA and OA.…”
Section: Discussionsupporting
confidence: 89%
“…Further supporting this notion, serum CXCL12 levels were positively correlated with the titers of RF, which is produced by synovial B cells in response to the local environment in the rheumatoid joint. 43 Given that the association of RF positivity with SSc arthropathy is also reported in a previous study, 44 our current data suggest that CXCL12 is involved in the de- with the CXCL12-G801A, rather than CXCL12-G801A itself, to the altered levels of transcripts. Importantly, the expression of CXCL12 and CXCR4 is enhanced in endothelial cells of early edematous SScinvolved skin compared with those of healthy control skin, but their expressions are progressively decreased in parallel with disease duration irrespective of disease subtype.…”
Section: Discussionsupporting
confidence: 83%
“…In fact, SSc-RA overlap is less common. The true rate of patients with SSc overlapped with RA is only 4.6%-6% (2,8) . In a research of 61 SSc patients, anti-CCP positive was observed only in patients with SSc-RA overlap (5) .…”
Section: Discussionmentioning
confidence: 94%
“…24-97% of patients with SSc developed arthritis during the course of the disease (5) . Anti-CCP antibodies and RF can be present in SSc patients, particularly in those with joint involvement, which may lead to misdiagnosis as RA on the early stage (2) . In fact, SSc-RA overlap is less common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation